2022
DOI: 10.1088/2053-1591/ac7287
|View full text |Cite
|
Sign up to set email alerts
|

Performance study of a new epoxy resin IR-3 in HTS-based high-field magnet application

Abstract: REBCO (Rare-earth-based barium copper oxide) conductors are appropriate materials for high-field magnet applications. Vacuum impregnation using epoxy resin is a technique widely used for stable operation of superconducting coils. However, epoxy-impregnated REBCO coils often experience critical current degradation problems. Finding a suitable impregnating material for REBCO coils is important for their application in high-field superconducting magnets. A new toughness epoxy, IR-3, was developed recently. An in-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Because the tensile radial stress is mainly caused by the thermal expansion coefficient (CTE) mismatch between the REBCO CC and the epoxy resin layer in the epoxy impregnated REBCO pancake coil. In this regard, the investigation showed that the thermal stress can be reduced by modifying the CTE of the epoxy resin by adding fillers to the epoxy resin [38][39][40][41]. Meanwhile, the overband fabrication technology is also widely used in the epoxy impregnated REBCO pancake coil or no-insulation REBCO coil to reduce the radial and hoop stresses [42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…Because the tensile radial stress is mainly caused by the thermal expansion coefficient (CTE) mismatch between the REBCO CC and the epoxy resin layer in the epoxy impregnated REBCO pancake coil. In this regard, the investigation showed that the thermal stress can be reduced by modifying the CTE of the epoxy resin by adding fillers to the epoxy resin [38][39][40][41]. Meanwhile, the overband fabrication technology is also widely used in the epoxy impregnated REBCO pancake coil or no-insulation REBCO coil to reduce the radial and hoop stresses [42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…The interlayer reinforcement material of the coil conductor generally Materials 2023, 16, 5828 2 of 12 uses Zylon, and the outer layer reinforcement uses glass fiber [7]. Finally, the whole coil is reinforced with epoxy resin and fixed [8]. The forming coil adopts the reinforcement technology of the pulse magnet to improve the overall strength.…”
Section: Introductionmentioning
confidence: 99%